Cremation and Christianity: English Anglican and Roman Catholic attitudes to cremation since 1885 - Knight, Frances (Taylor & Francis, 2017)
Britain was the first modern European country to adopt the widespread practice of cremation, and by 2010, it took place in around three-quarters of all funerals. Although the clergy had ceased to be the exclusive custodians of funeral ritual, their views and example remained highly significant in conveying approval, or disapproval, of cremation to their religious constituencies. This article explores attitudes to cremation amongst the English Anglican and Roman Catholic leadership in the twentieth century. In the first half of the century, a number of high-profile Anglican bishops promoted cremation by both teaching and example. The Roman Catholic Church, however, remained opposed to the practice, which it equated with atheism and inhumanity. Although the Catholic position began to soften from the 1960s, it is evident that some reticence about cremation remains. The different approaches to cremation illuminate a subtle religious and cultural fault line between the two ecclesial communities which has hitherto been little explored. The article highlights the role of the Cremation Society of Great Britain in working with members of both Churches to normalise cremation.